Tislelizumab plus nimotuzumab is effective against recurrent or metastatic oral squamous cell carcinoma among patients with a performance status score ≥ 2: a retrospective study - Wu, Wen-Jie; An, Pu-Gen; Zhong, Yi-Wei; Hu, Xiao; Wang, Lin; Zhang, Jie (Frontiers in Oncology, 2024)
The efficacy of treatments targeting recurrent or metastatic head and neck squamous cell carcinoma are unsatisfactory in practice for patients with a ECOG PS score ≥ 2. Thus, this study retrospectively evaluated the safety and efficacy of a programmed cell death 1 inhibitor (tislelizumab) combined with an epidermal growth factor receptor inhibitor (nimotuzumab) in treating patients with a PS score ≥ 2 who suffer from recurrent or metastatic oral squamous cell carcinoma (OSCC).: Fifteen patients were treated with tislelizumab (200 mg IV Q3W) and nimotuzumab (200 mg IV Q3W). Programmed cell death-ligand 1 (PD-L1) expression in tumor biopsies was assessed with immunohistochemistry. Whole-exome sequencing was used to evaluate treatment efficacy based on PD-L1 expression and gene mutation.Results: At a median follow-up of 9.6 months, median overall survival was 10.1 months, and median progression-free survival was 4.0 months. Overall response rate was 40%, with 6/15 patients achieving partial response. Eight patients exhibited nine adverse events, eight out of nine being grade 2 and the remaining being grade 3. Wholeexome sequencing showed that DYNC1I2, THSD7A, and FAT1 mutations were associated with patient prognosis.Combination therapy involving tislelizumab plus nimotuzumab is a promising, low-toxicity treatment for recurrent or metastatic OSCC in patients with a PS score ≥ 2.